Continuous Improvement in enhancing quality - Prembayun, Kunthi Widhi Prembayun (UHN IGB Sugriwa Denpasar, 2025)
This study examines the application of continuous improvement in improving the quality of education through the Total Quality Management (TQM) approach with the Plan-Do-Check-Action (PDCA) cycle method. The results show that continuous improvement is able to improve the quality of academic services, maintain accreditation, and adapt to the needs of the times. Successful implementation is supported by the establishment of a quality council, clear statements of responsibility, adequate infrastructure, as well as a data-driven approach and involvement of all parties. The findings confirm the importance of regular evaluation and an adaptive organizational culture to ensure the sustainability of quality improvement programs. Keyword: Continuous Improvement, TQM, PDCA, Education Quality.